1999
DOI: 10.1099/00222615-48-2-133
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterisation of neurotoxigenic Clostridium butyricum from soil in China

Abstract: Soil specimens collected from a site around the home of patients with food-borne type E botulism probably caused by neurotoxigenic Clostridium butyricum in Guanyun, Jiangsu province, China, were examined for the presence of neurotoxigenic C. butyricum. Five lakeside sites of Weishan lake, in an area near to the sites where the type E botulism outbreaks caused by neurotoxigenic C. butyricum occurred were also surveyed. Type E toxin-producing C. butyricum was isolated from soil from four sites including the site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 11 publications
0
43
0
Order By: Relevance
“…In 1997, we isolated BoNT/E-producing C. butyricum from the food implicated in food-borne botulism in China (10). Because our results indicated that type E food-borne botulism can be caused by BoNT/E-producing C. butyricum, we reexamined the cultural and biochemical properties of BoNT/E-producing organisms that had previously been isolated from type E food-borne botulism cases and found that two isolates were identifiable as C. butyricum (9). In addition, we isolated several strains of BoNT/E-producing C. butyricum from soil specimens of China (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 1997, we isolated BoNT/E-producing C. butyricum from the food implicated in food-borne botulism in China (10). Because our results indicated that type E food-borne botulism can be caused by BoNT/E-producing C. butyricum, we reexamined the cultural and biochemical properties of BoNT/E-producing organisms that had previously been isolated from type E food-borne botulism cases and found that two isolates were identifiable as C. butyricum (9). In addition, we isolated several strains of BoNT/E-producing C. butyricum from soil specimens of China (9).…”
mentioning
confidence: 99%
“…Because our results indicated that type E food-borne botulism can be caused by BoNT/E-producing C. butyricum, we reexamined the cultural and biochemical properties of BoNT/E-producing organisms that had previously been isolated from type E food-borne botulism cases and found that two isolates were identifiable as C. butyricum (9). In addition, we isolated several strains of BoNT/E-producing C. butyricum from soil specimens of China (9). In 1998, an outbreak of food-borne botulism was reported in India and was strongly suggested to be caused by BoNT/E-producing C. butyricum (2).…”
mentioning
confidence: 99%
“…In Italy, the toxigenic C. butyricum type E strains have been associated with infant cases, while the toxigenic C. butyricum type E strains in China have been associated either with food-borne botulism in food products such as fermented soybean paste or with environmental samples (2,20,21,27). Comparison of C. butyricum type E strains by various methods, including randomly amplified polymorphic DNA (RAPD), pulsed-field gel electrophoresis (PFGE), and bont/E gene sequencing, divided the strains into three clusters: strains associated with (i) infant botulism cases in Italy, (ii) food-borne botulism cases in China, and (iii) soil specimens from the Weishan Lake area in China (22). The results showed the conservation among the C. butyricum type E strains, suggesting a clonal distribution (27).…”
mentioning
confidence: 99%
“…C. botulinum and neurotoxigenic C. butyricum share the ability to produce botulinum neurotoxin E, while both C. botulinum and neurotoxigenic C. baratii can produce botulinum neurotoxin F; the differentiation of the three species by conventional methods is rather difficult (13,23). Neurotoxigenic C. butyricum type E has been implicated in infectious botulism (2,10) and has recently been shown to be an emergent food-borne pathogen (1,25,26,28); indeed, like C. botulinum, it can grow and produce toxin in food under favorable conditions (1). In Italy, C. butyricum type E appears to be more widespread than C. botulinum type E, based on isolation from several cases of botulism (9).…”
Section: Resultsmentioning
confidence: 99%
“…Neurotoxigenic C. butyricum type E strains JP/LCL155 and JP/KZ1890 were kindly provided by Shinichi Nakamura, Kanazawa University, Japan: they had been isolated from food (JP/LCL155) and soil (JP/KZ1890) samples isolated during investigation of two different outbreaks of food-borne botulism in China (25,26). The remaining C. butyricum type E strains had been isolated in Italy from clinical samples from patients suffering from botulism (1,2,10).…”
Section: Methodsmentioning
confidence: 99%